Open Access in Southern European countries - Abad García, María Francisca (2010)
The Spanish Foundation for Science and Technology (FECYT) is a public foundation under the Spanish Ministry of Science and Innovation whose mission is to strengthen the value chain of knowledge by fostering science and innovation and trying to integrate them and bring them closer to society, in response to the needs and expectations of the Spanish science, technology and enterprise system. The Foundation’s goal is to be recognized by Spanish society as a key reference in the dissemination, information and measurement of science and innovation. It also wishes to contribute to the development of a knowledge-based economy. One of the main challenges of the Foundation is to lead the integration and rationalization of scientific information and science, technology and innovation metrics, described as the “integrate and measure vector” in its 2010- 2012 strategic plan. FECYT already has considerable experience in managing national scientific information. It is the national licensee of the Thomson Reuters Web of Knowledge accessed by the Spanish scientific community. It is also firmly committed to establishing itself as the Spanish hub in favour of the open access (OA) movement (for free access to scientific information available on the Internet), in combination with supporting the traditional markets of scientific information. In 2010 FECYT organized the 5th International Conference on Open Repositories in Madrid, with the aim of positioning Spain in the debate on emerging trends in the management of scientific information. The authorities are opening the door to the open access movement, under the belief that publicly funded research should be freely available. Among other initiatives, the 2010 Spanish Bill on Science, Technology and Innovation urges researchers to deposit their research papers produced with public funding in institutional repositories.